Influence of Socket-shield technique on the biomechanical response of dental implant: three-dimensional finite element analysis - Tribst, João Paulo Mendes [UNESP]; Dal Piva, Amanda Maria de Oliveira [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Bottino, Marco Antonio [UNESP] (Taylor & Francis, 2020)
This study evaluated the bone microstrain, displacement, and stress distribution according to the surgical technique (conventional or Socket-shield) and evaluation period (immediately after implant installation or after healing). Each condition was modeled for the finite element analysis, totaling four groups, with a morse-taper implant and a cemented prosthesis. The maximum displacement, von Mises stress, and bone microstrain yielded higher values during the immediate stage, without a difference between Socket-shield and conventional treatments. The use of the Socket-shield technique does not negatively impact the biomechanical behavior of an implant-supported prosthesis immediately after healing from the implant installation.
Keywords: Finite element analysis; implants; prosthetic dentistry